A PERFORMANCE INTERPRETATION OF THE VIENNESE CLASSICS BY THE EXAMPLE OF FANTASIA FOR PIANO, CHORUS AND ORCHESTRA IN C MINOR, OP. 80 BY LUDWIG VAN BEETHOVEN - BYELIK-ZOLOTAROVA, Nataliya; ZOLOTARYOVA, Natalya; BOIKO, Viacheslav; SUKHOMLINOVA, Tetiana; ZAVERUKHA, Olena (Studia Universitatis Babes-Bolyai Musica, 2023)
The relevance of the study is determined by the need to cover the significance, uniqueness and means of performance of one of the masterpieces of the Viennese Classical School — Fantasia in c minor, op. 80 for mixed choir, piano and orchestra by Beethoven. The aim of this publication was to study the problems of performance interpretation of the legacy of the Viennese Classical School using the example of L. Beethoven’s Fantasia for piano, soloists, mixed chorus, and orchestra. Research methods were: creation of an information background; comparative analysis and structuring of information; identification of the categories that make the basis of the problem; generalization of obtained data. The materials based on audio and video recordings of the work by prominent representatives of the performing arts were used. The literature on the stylistic and compositional atmosphere of the era of Viennese classicism, as well as on features of the genres of the work was also used. The results of the study revealed the interrelationship of all components of the problem being studied. They evidenced the inseparability of such elements as genre, musical form, instrumentation, manner of performance, a certain historical period, as well as the stylistic orientation prevailing within it. Its main categories were identified while studying the chosen topic, as well as their dependency on the temporal, stylistic, individual, and psychological (performers’ personalities) context was established. These facts became a theoretical and methodological contribution to art science, history of performance, as well as music pedagogy. As a conclusion of the study on performing interpretation of the Viennese classics using the example of Fantasia by Beethoven, its genre stylistic and compositional technical universality was determined; the process during which the piano becomes a solo concert instrument; the role of improvisation in the large-scale synthetic genre; development of a single performance concept by the conductor, pianist and choirmaster, diversity of artistic and psychological types of performance while preserving the main author’s idea. The research of this topic has wide prospects in the future, thanks to its volume, multi-vector nature, connection with a wide range of musical subjects, and sensitivity to individual styles of interpretation in the context of different epochs. This is emphasized by the value of classical heritage, the need to preserve and popularize it.